A systematic review and narrative synthesis of footwear and orthotic devices used in the management of ankle haemarthrosis and haemarthropathy in haemophilia - Wilkins, Richard A.; Chapman, Lara S.; Emmel, Jenny C.; Flannery, Thuvia; Chapman, Graham J.; Walwyn, Rebecca E. A.; Redmond, Anthony C.; Siddle, Heidi J. (Haemophilia : the official journal of the World Federation of Hemophilia, 2022)
Introduction Haemarthrosis is a clinical feature of haemophilia leading to haemarthropathy. The ankle joint is most commonly affected, resulting in significant pain, disability and a reduction in health‐related quality of life. Footwear and orthotic devices are effective in other diseases that affect the foot and ankle, such as rheumatoid arthritis, but little is known about their effect in haemophilia. Aims To review the efficacy and effectiveness of footwear and orthotic devices in the management of ankle joint haemarthrosis and haemarthropathy in haemophilia. Methods A systematic literature review was conducted. Two review authors independently screened studies for inclusion and appraised methodological quality using Joanna Briggs Institute Critical Appraisal checklists. A narrative analysis was undertaken. Results Ten studies involving 271 male participants were eligible for inclusion. All studies were quasi‐experimental; three employed a within‐subject design. Two studies included an independent comparison or control group. A range of footwear and orthotic devices were investigated. Limited evidence from non‐randomised studies suggested that footwear and orthotic devices improve the number of ankle joint bleeding episodes, gait parameters and patient‐reported pain. Conclusion This review demonstrates a lack of robust evidence regarding the efficacy and effectiveness of footwear and orthotic devices in the management of ankle joint haemarthrosis and haemarthropathy in haemophilia. Methodological heterogeneities and limitations with the study designs, small sample sizes and limited follow‐up of participants exist. Future studies utilising randomised designs, larger sample sizes, long‐term follow‐up and validated patient‐reported outcome measures are needed to inform the clinical management of ankle joint haemarthrosis and haemarthropathy.